Public health insurance and entry into self-employment - Frank M. Fossen; Johannes König (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2015)
We estimate the impact of a differential treatment of paid employees versus self-employed workers in a public health insurance system on the entry rate into entrepreneurship. In Germany, the public health insurance system is mandatory for most paid employees, but not for the selfemployed, who usually buy private health insurance. Private health insurance contributions are relatively low for the young and healthy, and until 2013 also for males, but less attractive at the other ends of these dimensions and if membership in the public health insurance allows other family members to be covered by contribution-free family insurance. Therefore, the health insurance system can create incentives or disincentives to starting up a business depending on the family situation and health. We estimate a discrete time hazard rate model of entrepreneurial entry based on representative household panel data for Germany, which include personal health information, and we account for non-random sample selection. We estimate that an increase in the health insurance cost differential between self-employed workers and paid employees by 100 euro per month decreases the annual probability of entry into selfemployment by 0.38 percentage points, i.e. about a third of the average annual entry rate. The results show that the phenomenon of entrepreneurship lock, which an emerging literature describes for the system of employer provided health insurance in the USA, can also occur in a public health insurance system. Therefore, entrepreneurial activity should be taken into account when discussing potential health care reforms, not only in the USA and in Germany.
Keywords: L26; I13; J2; 330; health insurance; entrepreneurship lock; self-employment